(untitled) (Agro Productividad, 2025)
Objective: to evaluate the effect of sex ratio on reproductive aspects of dwarf crayfish (Cambarellus montezumae) in aquaculture recirculating systems. Design/ Methodology/ Approach: three treatments with female-to-male sex ratios (2:1, 3:1, and 5:1) were used. The organisms were collected from the wild, acclimated, and subsequently placed into a recirculating aquaculture system. Reproductive variables such as the number of fertilized eggs and the number of offspring released per female were measured. Results: sex ratio had no effect (p > 0.05) on fecundity, fertility, or frequency of ovigerous (egg-bearing) females per treatment. Fertilization rate exceeded 50%. This suggest the existence of other independent factors (either on females or males) which contribute to reproductive success. Limitations/ Implications of the study: this study confirms the polygamous behavior of males, which is a characteristic of other crustacean. It is found, then, that reproduction can be optimized by modifying female to male ratios. In addition to considering factors such as water quality, female size, and environmental conditions. Findings/ Conclusions: sex ratio is not a key factor for improving Montezuma dwarf crayfish reproduction in controlled systems. We recommend prioritizing the optimization of environmental conditions, and selecting high-quality broodstock to increase reproductive efficiency